ANALISIS PENGUKURAN TINGKAT KESIAPAN IMPLEMENTASI KNOWLEDGE MANAGEMENT PADA SMP MUHAMMADIYAH 1 PRINGSEWU LAMPUNG - Isnandar, Saiful; Budi, Indra (244-5567)
The research was carried out to get an overview of the extent to which the level of school readiness in applying knowledge management so that the utilization of information technology can bring many benefits in all aspects for the Betterment of mankind. So that the knowledge can be used to its full potential, then the school is in need of a system that is capable of managing knowledge is often called knowledge management system. Through this system, members of the school can exchange knowledge with each of the parties who are in school, so as to provide benefits like the idea, theidea to new innovations that can provide improved performance in school. This measurement is done by typing a few Knowledge Management Critical Success Factor into the aspects of Knowledge Management including aspects of Abstrarct, Soft and Hard. From the results of theanalysis of the data, then it can be inferred that the JUNIOR HIGH SCHOOL Muhammadiyah 1 Pringsewu are at level 3 (Knowledge-Enabled), which means that the Organization has been ready to do the application of knowledge management.Keywords: Knowledge, Knowledge Management, Knowledge-Enabled